Energy efficient refurbishment towards nearly zero energy houses, for the mediterranean region - Serghides, Despina Kyprianou; Dimitriou, Stella; Michaelidou, Maria; Katafygiotou, Martha (My University, 2015)
The building sector in Europe is responsible for an estimated 40% of the total energy consumption and 10% of the total CO2 emissions. Given that new buildings represent only about 1% of the housing stock annually, it is estimated that more than 80% of the existing buildings will still exist in 2020. Therefore, the energy efficient renovation of the existing housing stock is imperative in order to reduce the building energy consumption. It is for this reason that the European Union ranked the improvement of the energy performance of the old building stock, as a high priority in its research agenda. Following Europe's 20:20:20 objective, this case study investigates refurbishment scenarios in order to achieve Nearly Zero Energy houses, in Cyprus. The research focuses on the Single Family House typology, as classified in previous studies for Cyprus, in the framework of the IEE, EU project EPISCOPE and specifically on retrofitting an old house that was built before 1980. The aim is to upgrade it into a Nearly Zero Energy Building (nZEB) with the implementation of the national energy performance requirements, as drafted by the Ministry of Energy, Commerce, Industry and Tourism (MECIT). Following the EPISCOPE project methodology, a representative Single Family House from the corresponding residential building typology in Cyprus was chosen and modeled using the iSBEMcy tool. This is the official governmental software in Cyprus used for issuing Energy Performance Certificates (EPC), for the categorization of the energy class of the building and the calculation of the CO2 emissions according to the European Directives 2002/91/EC and 2010/31/EC. The study investigates whether it is possible for an old Single Family House to reach the nZEB standards and identifies the lurking obstacles and challenges, through building simulations. To this end, various refurbishment scenarios were developed, with the implementation of strategies aiming at fulfilling the MECIT requirements. Through analysis of the results, the efficiency of each strategy and technique employed towards minimising the energy consumption and the greenhouse gas emissions was evaluated, in terms also of its cost effectiveness. Furthermore, the results of the research were investigated in order to assess whether the nZEB requirements, as developed by the MECIT, are appropriate for the existing single-family houses in Cyprus and whether alternative strategies may be employed in order to meet the target of nZEB and to reduce effectively the energy consumption.
Keywords: Energy performance; Existing single housing typology; Nearly zero energy buildings; Old houses